2006
DOI: 10.2135/cropsci2005.12-0500
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Glycine Germplasm for Nulls of the Immunodominant Allergen P34/Gly m Bd 30k

Abstract: Soybean [Glycine max (L.) Merr.] seed contains an immunodominant human allergen P34 or Gly m Bd 30k (mentioned as P34) of the cysteine protease family. of approximately 16 266 accessions from USDA soybean germplasm screened, 12 P34 null lines were identified among soybean (G. max), wild annual (Glycine soja Sieb. and Zucc.), and wild perennial Glycine spp. Glycine soja were low P34 expressers, while G. max and wild perennial species had nondetectable levels of the allergenic protein. Further investigation of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 29 publications
2
64
3
Order By: Relevance
“…These findings seem to cast doubt on the previous reports that the soybean P34/Gly mBd 30K allergen is the most immunodominant allergen in the population (Ogawa et al 1991;Joseph et al 2006) since several other proteins are as significant, if not more significant, in this cohort. Some early reports of soy allergen identification by Western blot have used sera from children (Ogawa et al 1991); however, our study has demonstrated that, although this protein was frequently detected by adult IgE, it was not responsible for intense reactions (see band 11 on Fig.…”
Section: Frequency Of Patient Reactions Against Soy Proteinscontrasting
confidence: 80%
See 1 more Smart Citation
“…These findings seem to cast doubt on the previous reports that the soybean P34/Gly mBd 30K allergen is the most immunodominant allergen in the population (Ogawa et al 1991;Joseph et al 2006) since several other proteins are as significant, if not more significant, in this cohort. Some early reports of soy allergen identification by Western blot have used sera from children (Ogawa et al 1991); however, our study has demonstrated that, although this protein was frequently detected by adult IgE, it was not responsible for intense reactions (see band 11 on Fig.…”
Section: Frequency Of Patient Reactions Against Soy Proteinscontrasting
confidence: 80%
“…In fact, preliminary results of patient serum screening on 2D gels would seem to indicate that these two allergens are not major or are not being detected by 2D gel screening (data not shown). We are presently making use of a recently discovered P34-null germplasm to further investigate these North American patients (Joseph et al 2006). Although this group of patients is relatively small in number, it suggests a trend with regard to the soybean proteins most likely to provoke allergic reactions among North Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the techniques adopted for reducing toxins and allergens, usually transgenesis shows superior characteristics: it is not only more efficient in obtaining the desired phenotype (both in time and trial numbers) but also more precise. Natural null mutants for the P34 soybean allergen [117] have a frequency of 2/14,000 in cultivated soybean, that is 0.014%, and the exact reason for the lack of P34 is uncertain. Conversely, the frequency of soybeans coming out of a transformation showing P34 cosuppression is in the 10-20% range (E. Herman, pers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore an alternative approach was used to achieve the same goal: identify soybeans lacking the allergen. The entire USDA national soybean germplasm collection was screened and out of more than 16,000 accessions screened, they found 12 lines (2 of which are cultivated soybean) with no P34 allergen [117]. Based on the sequence analysis, it is possible to guess the reason why these soybean plants lack the allergen.…”
Section: Examples Of Inactivation Of Allergens In Transgenic Plantsmentioning
confidence: 99%
“…Of the approximately 16,266 soybean accessions from the USDA germplasm collection that were screened, only two were found to have reduced P34 protein accumulation in seeds (Joseph et al 2006). The low P34 soybean accessions PI 567476 and PI 603570A were characterized as having normal levels of seed proteins other than P34 (Joseph et al 2006).…”
Section: Introductionmentioning
confidence: 99%